Strategi Kepala Sekolah dalam Meningkatkan Mutu Akademik di SMKS Plus Al-Ma’arif Kota Malang - Mubin, Holikul; Aqila Al Gandhi, Evita Reyssa; Fatih, Puteri Nur; Yaqien, Nurul (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is a fundamental foundation for developing quality human resources. However, Vocational High Schools (SMKs) face various challenges, including low student academic achievement, a lack of teacher motivation, and limited facilities and infrastructure. The principal plays a central role in improving academic quality through the implementation of effective strategies to produce competent and job-ready graduates. This study employs a descriptive qualitative approach, utilizing interviews, observations, and documentation for data collection. The findings reveal that the strategies employed by the principal of SMKS Plus Al-Ma’arif Kota Malang to enhance academic quality include teacher development, collaborative benchmarking programs, and community involvement. These findings can serve as a model for other vocational schools in efforts to improve the quality of vocational education. Furthermore, this study provides recommendations for policymakers in formulating more effective programs to enhance vocational education quality.